2020
DOI: 10.1101/2020.09.10.288902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ribosome stalling caused by the Argonaute-microRNA-SGS3 complex regulates the production of secondary siRNAs in plants

Abstract: The path of ribosomes on mRNAs can be impeded by various obstacles. One such example is halting of ribosome movement by microRNAs, though the exact mechanism and physiological role remain unclear. Here, we find that ribosome stalling caused by the Argonaute-miRNA-SGS3 complex regulates production of secondary siRNA biogenesis in plants. We show that the double-stranded RNA-binding protein, SGS3, directly interacts with the 3′ end of the microRNA-Argonaute complex, resulting in ribosome stalling. Strikingly, mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…In plants, 22-nt siRNAs can repress translation, leading to induction of transitive small-RNA amplification by RNA-dependent RNA polymerase 6 (RDR6) 62 . Another recent report in plants showed that microRNA targeting recruits a double-strand RNA binding protein, which induces ribosome stalling, and the ribosome stalling enhances the generation of secondary small RNAs 63 . Therefore, we propose that the regulation of small-RNA biogenesis by ribosome occupancy and codon usage of the target transcript might be a general strategy adopted across evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, 22-nt siRNAs can repress translation, leading to induction of transitive small-RNA amplification by RNA-dependent RNA polymerase 6 (RDR6) 62 . Another recent report in plants showed that microRNA targeting recruits a double-strand RNA binding protein, which induces ribosome stalling, and the ribosome stalling enhances the generation of secondary small RNAs 63 . Therefore, we propose that the regulation of small-RNA biogenesis by ribosome occupancy and codon usage of the target transcript might be a general strategy adopted across evolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, a fundamental difference is that the latter involved the degradation of the silenced transcripts, while CaMV silencing acts on translation efficiency but not RNA degradation. Translational repression through ribosome stalling especially during stress adaption has recently emerged as a major function of RNA silencing (Kim et al ., 2021; Iwakawa et al ., 2020; Wu et al ., 2020). Combining the concept of substrate channeling and competition between PBs and siRNA bodies (Jouannet et al ., 2012) with a viral infection context, we suspect that the association of PB components with CaMV VFs reduces viral RNA template acquisition by the RDR6 silencing machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Several PB proteins were shown to regulate viral infections; Carbon Catabolite Repression 4 (CCR4) facilitates Barley yellow striate mosaic virus replication in barley (Zhang et al ., 2020), VCS supports Potato virus A infection (De et al ., 2020; Hafrén et al ., 2015) and overexpression of several PB components was shown to restrict Turnip Mosaic Virus (Li & Wang, 2018) . It is becoming increasingly evident that RNA surveillance pathways, including RNA silencing and decapping, play a major role in translational regulation not only through degradation of aberrant RNAs, but by eliciting translational repression on endogenous targets (Hung & Slotkin, 2021; Iwakawa et al ., 2020; Wu et al ., 2020; Jang et al ., 2019; Lanet et al ., 2009; Xu & Chua, 2009; Brodersen et al ., 2008). As part of antiviral translational regulation, different animal viruses are frequently challenged with a global shut-down of protein production.…”
Section: Introductionmentioning
confidence: 99%
“…Ribosome profiling experiments demonstrate ribosome association with TAS precursors (73,74), and loss of the exportin-like protein SDE5 required for all tasiRNA production causes loss of TAS precursor transcripts from ribosome-associated fractions (75). Furthermore, detailed biochemical analyses reveal the importance of ribosome stalling in proximity to the 5’ miR390 site in TAS3 precursors (74), and ribosome stalling and collision at rare codons in transposable element mRNAs correlates with their production of 21-nt siRNAs (53) (observed in mutants defective in DNA methylation, and, therefore, often referred to as epigenetically activated siRNAs, or easiRNAs (25)). It appears, therefore, that stalled ribosomes, in particular in combination with RISC, act as a trigger of secondary siRNA production, perhaps by extending the time of RISC association with target mRNA by AGO interaction.…”
Section: Discussionmentioning
confidence: 99%